THE EXORCISM DESCRIBED IN JAMES WAN'S FILM THE CONJURING - Haryati Sulistyorini (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
The paper entitled The Exorcism described in James Wan's Film, The Conjuring has an objective to describe a problem dealing with demonic possessed and exorcism. The object used here is a horror film, since the whole tension of the story is about misery and haunted. Exorcism is a spiritual practice used to help people who experiences demonic possessed. Lorraine and Ed as the main characters here are described as demonologists or paranormal investigators who help the Perron's family from the demonic possessed. The terror happened in the old haunted house in Rhode Island brings Carolyn, Peron's wife into a mental illness and it cannot be handled by a doctor's hand except a spiritual practice like exorcism. After it has been approved by the Priest of the church, finally the exorcism was done by the demonologist or paranormal investigators Lorraine and Ed. They are described as the main character of the story. During the exorcism they experience both internal and external conflict and it develops becomes the potential conflict. The tension of the story is finally resolved when the main characters did the spiritual practice/the exorcism well. Finally it can be seen that problems dealing with the demonic possessed only can be handed by the spiritualpractice like exorcismKeywords: exorcism, demonologist, demonic possessed,